1981
DOI: 10.1289/ehp.8138119
|View full text |Cite
|
Sign up to set email alerts
|

Chemical suppression of steroidogenesis.

Abstract: A large number of chemicals are known to interfere with steroidogenesis in the adrenal cortex and other tissues. Many xenobiotics inhibit steroid hormone production as a result of interactions with cytochrome P-450-containing hydroxylases in adrenal mitochondria or microsomes. For example, metyrapone, a compound used clinically in the evaluation of pituitary-adrenocortical function, binds to various cytochromes P-450 in the adrenal, preventing the interactions of steroid substrates with the enzymes and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…At the same time, through the rate of progesterone to 17α-hydroxyprogesterone and 21-hydroxyprogesterone, the activities of adrenal 17α-hydroxylase and 21-hydroxylase were detected, with a 50% to 80% loss, similar to the heme concentration of cytochrome P-450. Similarly, Colby's study [8] showed that both SL and canrenone could concentration-dependently inhibit microsomal 21-hydroxylation and mitochondrial 11β-hydroxylation, although the effect of canrenone was better when using mitochondria and microsomes derived from guinea pig adrenal glands.…”
Section: Impeditive Effect On Aldosterone Steroidogenesismentioning
confidence: 84%
See 1 more Smart Citation
“…At the same time, through the rate of progesterone to 17α-hydroxyprogesterone and 21-hydroxyprogesterone, the activities of adrenal 17α-hydroxylase and 21-hydroxylase were detected, with a 50% to 80% loss, similar to the heme concentration of cytochrome P-450. Similarly, Colby's study [8] showed that both SL and canrenone could concentration-dependently inhibit microsomal 21-hydroxylation and mitochondrial 11β-hydroxylation, although the effect of canrenone was better when using mitochondria and microsomes derived from guinea pig adrenal glands.…”
Section: Impeditive Effect On Aldosterone Steroidogenesismentioning
confidence: 84%
“…SL has been reported to inhibit aldosterone synthesis in the adrenal cortex and aldosterone antagonism in the periphery. Inhibition of hormone synthesis has been reported for 11β-hydroxylase [6][7][8][9], 21-hydroxylase [8][9][10][11], 18-hydroxylase [6,7], and 17α-hydroxylase [10][11][12][13] (Table 1). The inhibitory effect of SL is thought to be due to the disruption of cytochrome P450 in steroidsynthesizing cells [9].…”
Section: Inhibition Of Steroid Hormone Synthesis By Mineralocorticoid...mentioning
confidence: 99%
“…The inhibitory effects of spironolactone on aldosterone production have been observed in a variety of in vitro cell culture and in vivo animal model systems [2123, 53]. These observations can be explained by previous studies that described the ability of spironolactone to bind and inhibit steroidogenic cytochrome P-450 enzymes (including 18, 17- and 21-hydroxylase activities) [24, 50, 54]. There are no studies that suggest that spironolactone inhibition of steroidogenesis is due its effects on MR. As noted above, the concentrations needed to effectively inhibit steroid production (10 and 30 µM spironolactone) were far greater than the amounts needed to inhibit MR activation.…”
Section: Discussionmentioning
confidence: 98%
“…There is, however considerable evidence that spironolactone inhibits adrenal cell aldosterone production [2023]. It is also well documented that spironolactone binds and blocks cytochrome P450 enzymes involved in steroidogenesis [2426]. …”
Section: Introductionmentioning
confidence: 99%
“…It is known that spironolactone can bind to and inhibit steroidogenic cytochrome P450 enzymes. 18 It has recently been demonstrated that in human adrenocortical H295R cells, spironolactone inhibited steroid production while eplerenone had no effect on production of aldosterone or cortisol in this system. Furthermore, the metabolic instability of steroids in the presence of CYPs can affect the magnitude and duration of action and can alter their pharmacological and toxicological profiles in relevant organs.…”
Section: ■ Steroidogenesis Hypothesismentioning
confidence: 89%